Representasi Tipe Kepribadian Ekstrover Pada Novel Anak Hwaiting dan Little Ballerina Karya Muthia Fadhilla Khairunnisa: Kajian Psikologi Carl Gustav Jung - Zhanen Arofani Wakhid (ELite Journal : International Journal of Education, Language, and Literature, 2018)
This research have focus on human personality in extrovert personality. Dwilogy Hwaiting and trilogy Little Ballerina novel by Muthia Fadhilla Khairunnisa are the objects of this research. This research is study of literary psychology by Carl Gustav Jung. Three focus on this research are extrovert personality type, motivation, and how to solve personality problem. This research is kualitative research that using descriptive analyzes method. The result of this research are: (1) there are four combination type extrovert-thinking, extrovert-feeling, extrovert-sensing, and extrovert-intuiting; (2) progression motivating factors; and (3) how to solve the personality problems like contradict-supporting-and unity..Keywords:    Extrovert, Children Novel, Pychology Literature